Definitions need to be precise and consistent: A reply to Haslam with suggestions for the future. Issue 2 (4th March 2017) - Cypryańska, Marzena; Nezlek, John B.; Jaskółowska, Aleksandra; Formanowicz, Magdalena Maria
ABSTRACT: In his reply to our critique of research on self-humanizing, Haslam claims that we used a narrow definition of self-humanizing that ignored the evidence from the correlational research he and his colleagues have done. We disagree. First, we relied upon a definition of self-humanizing based upon comparative judgments that Haslam and colleagues have consistently used. Second, we were well aware of the correlational research he and his colleagues have done. We simply did not think, and do not think, these correlations verified the existence of self-humanizing as defined. In his reply, Haslam offered a new definition of self-humanizing that defines self-humanizing in terms of correlations between comparative judgments and ratings of how much traits reflect human nature. Although we believe this change represents some progress, numerous issues in the study of self-humanizing remain to be resolved. We offer some suggestions for future research on this important topic.